The Perceptions of English Teachers on the Implementation of the Merdeka Curriculum in Idanogawo Schools - Marinus Zai (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The curriculum is an important component in the education system. Curriculum changes can be influenced by various factors, one of which is student learning outcomes. The interviews with English teachers regarding the implementation of the Merdeka curriculum in schools revealed various insights. The teachers expressed challenges in implementing the curriculum due to a lack of facilities and the recent initiation of the curriculum in their schools. They highlighted the potential of the Merdeka curriculum to improve English language learning by actively involving students in learning, enhancing critical thinking skills, and improving English language proficiency. The curriculum’s learner-centered philosophy was met with mixed responses, with some teachers expressing uncertainty about its implementation. However, others acknowledged the potential benefits of the curriculum, such as providing freedom to students and creating enjoyable education. The teachers also emphasized the importance of readiness in terms of educators’ competence, skills, and mindset, as well as the availability of infrastructure and facilities. Despite the challenges, they recognized opportunities for support from school principals, curriculum teams, and parents, as well as the positive use of technology in learning. Overall, the interviews reflected a range of perceptions on the Merdeka curriculum, highlighting both challenges and opportunities in its implementation.